Innocent until nominated : the breakdown of the presidential appointments process - MacKenzie, G. Calvin (Brookings Institution Press, 2011)
According to outspoken presidential scholar Cal Mackenzie, the presidential appointments process is a national disgrace. It encourages bullies and emboldens demagogues, silences the voices of responsibility, and nourishes the lowest forms of partisan combat. It uses innocent citizens as pawns in the petty games of politicians and stains the reputations of good people. It routinely violates fundamental democratic principles, undermines the quality and consistency of public management, and breaches simple decency. In short, at a time when the quality of political leadership in government matters.